The correlation between the interference colour and growth procedure of anodic titanium dioxide nanotube arrays. (30th November 2013) - Moon, Jongyun; Kemell, Marianna; Park, Byungki; Suominen, Arho; Mäkilä, Ermei; Punkkinen, Risto; Hedman, Hannu‐Pekka; Kim, Hong; Lassila, Lippo V; Tuominen, Aulis
<x xml:space="preserve">Abstract</x> Titanium dioxide nanotube arrays were anodised from titanium foils in an aqueous electrolyte solution of hydrofluoric acid. The formed oxide showed visually different colours owing to light interference in the titanium dioxide layer. The behaviour of interference colour in anodic titanium dioxide film was investigated by varying anodisation parameters such as the applied voltage and the anodisation time. The morphologies and the crystalline phases of anodised samples were studied on a field emission scanning electron microscope and X‐ray diffractometer. The correlation between the interference colour and growth procedure of anodic titanium dioxide nanotube arrays was studied. The anodic films prepared under different conditions consisted of a compact oxide film with a nanoporous/tubular structure upon/beneath it. The crystalline phase of the anodic oxide layer was amorphous. The optical properties of the oxide film were investigated on a spectrophotometer. Optical interference could be detected in compact oxide layers when the thickness of the titanium dioxide was as small as 70 nm. In general, the interferences of the nanoporous/tubular structures were lower than those for compact structures. The empirical colour properties were estimated by the L*a*b* system. The relationships between the interference colour of anodic titanium dioxide film and its thickness and morphology are discussed.